THE EFFECT OF HEADS’ LEADERSHIP AND NURSES’ JOB MOTIVATION ON NURSING PERFORMANCE IN THE HOSPITAL INPATIENT ROOM - Budi Hartono; Alfi Hidayati; Tri Kurniati; Nur'Aina Basir (Indonesian Journal of Health Administration, 2020)
Background: The fluctuated patient satisfaction level shows the need to improvenursing performance. Several factors that can improve nursing performance includeleadership, job motivation, management and environment. Leadership and job motivationbecome fundamental aspectsin improving employee performance. Aim: This study analyzedtherole of manager’s leadership and nurses’job motivation on nursing performance in the inpatient room ofthe Indonesian Red Cross Hospital Bogor.Methods: This study sampled a total of 150 nurses in the inpatient roomof the Indonesian Red Cross Hospital Bogorusing the incidental random sampling technique. This study employed a path analysis with three variables, such as manager’s leadership and job motivation as exogenous variables and nursing performance as an endogenous variable.Results: Leadership of the head of the inpatient room couldincrease job motivation and nursing performance.Conclusion: Manager’s leadership and job motivation could affect the level of nurses’ performancepartially and simultaneously. The Indonesian Red Cross Hospital Bogor could provide regular training to every head of the room to enhance their leadership and nurses’ job motivation. Keywords: leadership, job motivation, nurses’ work performance.